2006
DOI: 10.1103/physrevlett.97.018105
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Electron Attachment to Phosphoric Acid Esters: The Direct Mechanism for Single Strand Breaks in DNA

Abstract: We use dibutyl phosphate to simulate the behavior of the phosphate group in DNA towards the attack of low energy electrons. We find that the compound undergoes effective dissociative electron attachment within a low energy resonant feature at 1 eV and a further resonance peaking at 8 eV. The dissociative electron attachment (DEA) reactions are associated with the direct cleavage of the C-O and the P-O bond but also the excision of the PO-, PO3-, H2PO3- units. For the phosphate group coupled in the DNA network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 29 publications
(27 reference statements)
1
73
0
2
Order By: Relevance
“…We also intend to examine the possible role of shape resonances centered on the backbone, which have been proposed as an initial attachment mechanism leading to phosphodiester bond cleavage. 50,63,66 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also intend to examine the possible role of shape resonances centered on the backbone, which have been proposed as an initial attachment mechanism leading to phosphodiester bond cleavage. 50,63,66 …”
Section: Discussionmentioning
confidence: 99%
“…Condensedphase experiments on thymidine and a single-strand oligonucleotide have demonstrated that slow electrons do indeed break the C-O phosphate-sugar bonds as well as the C-N base-sugar bonds, [60][61][62] and C-O bond breaking was also found in gas-phase DA to a model phosphodiester. 63 A few electron-collision studies, experimental and theoretical, have looked at the individual backbone constituents, i.e., ribose or deoxyribose and a phosphate group, [64][65][66][67][68][69] and others have also been made of electron collisions with backbone analogs such as tetrahydrofuran, 29,65,[68][69][70][71][72][73][74][75][76][77][78][79] tetrahydrofurfuryl alcohol, 71,72,80,81 fructose, 79 and dibutyl phosphate. 63 However, the only electron collision measurements involving nucleosides that we are aware of are the study by Zheng et al of thymine desorption from condensed-phase deoxythymidine 60 mentioned earlier, and the gas-phase studies by Abdoul-Carime et al 82 and by Denifl et al 83 of DA to deoxythymidine and 5-bromouridine, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] In our earlier work we studied several saturated compounds containing the amino-and the hydroxyl groups which could be considered as model compounds for biomolecules. 11 We used the comparison between the HeI photoelectron spectra and the DEA spectra to identify the Feshbach resonances and to assign the DEA bands and found that all DEA bands could be explained by Feshbach resonances, the low-lying ones being localized on the functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is to use phosphoric acid derivatives bound to hydrocarbons as was done by Konig et al [69]. They used (C 4 H 9 O) 2 POOH because of its closeness in structure to DNA.…”
Section: Dissociative Electron Attachment (Dea) In Nucleobasesmentioning
confidence: 99%